Pengembangan Media Replika Istana Sultan Serdang Untuk Pemahaman Konsep Geometri Di Kelas V SD - Sri Wahyuni, Sukmawarti (Cybernetics: Journal Educational Research and Social Studies, 2022)
The problems in this study include the lack of interest in learning mathematics for students and the low understanding of students' geometric concepts. In addition, teachers also do not use the surrounding environment as a medium for learning geometry. The limited use of learning media also causes the learning process to not run effectively and students are not actively involved in learning. This study aims to develop a replica of the Sultan's Palace Serdang as a medium for learning mathematics on geometry concepts in elementary schools that are feasible and ready to be used. The research development model used in this study is a 4-D development model. The 4-D development procedure consists of a definition stage, a design stage, a development stage, and a deployment stage. This development procedure is adjusted to the guidelines for developing replica media so that at each stage it consists of several processes. The process at the definition stage includes: 1). Learning needs analysis; 2) See the completeness of the media. The process at the Design stage includes: 1). Develop learning media needs; 2). Create a predefined product design. The Development Phase includes: 1). Briefing by experts; 2). Validating learning media by material experts and media experts and teachers. The quality of the replica media that was developed based on the validation showed a good category. Create a predefined product design. The Development Phase includes: 1). Briefing by experts; 2). Validating learning media by material experts and media experts and teachers. The quality of the replica media that was developed based on the validation showed a good category. Create a predefined product design. The Development Phase includes: 1). Briefing by experts; 2). Validating learning media by material experts and media experts and teachers. The quality of the replica media that was developed based on the validation showed a good category.